Research on the Application Strategies of Activation from the Perspective of Human Resource Development in the Maintenance of Teachers’ Mental Health - Zhang, Qinyi (International Journal of Social Sciences and Public Administration, 2025)
In fact, a large number of teachers have poor mental health due to difficulties in work and life. Human resource development actually stimulates people’s autonomy and initiative, which can to some extent concretize psychological problems, control and solve mental illnesses, and independently manage negative emotions that arise in work and family. This article studies the application of activation in teachers’ mental health from the perspective of human resource development, and ultimately has innovative significance in forming strategies for maintaining teachers’ mental health.